PENGEMBANGAN MEDIA PEMBELAJARAN CANVA INTERAKTIF PADA MATERI JARING-JARING MAKANAN KELAS V SD - Achmad Fuad Syafi; Yusuf Setya Wardana; Fine Reffiane (STKIP Subang, 2026)
The low interest of students in learning science, including in the food web material, is caused by the lack of implementation of interactive learning media that integrates technological developments in the educational realm. The purpose of this study is to develop interactive Canva learning media that is in accordance with valid ADDIE rules and receives a good response from teachers and students. This type of research is research and development with the ADDIE development model. Data collection techniques include observation, interviews, and questionnaires. The data obtained were analyzed using quantitative descriptive to determine the validity value and analysis of teacher and student responses, as well as qualitative descriptive to describe suggestions and input from the validator. The results of the study indicate that the process of developing interactive Canva learning media is in accordance with ADDIE rules. The developed interactive Canva learning media is declared very valid with a material validation value of 91.7% and a media validation value of 97.5%. The media also received a very good response based on the results of the teacher response questionnaire of 92% and the results of the student response questionnaire of 93.2%. Thus, the results of the development of interactive Canva learning media can be said to be in accordance with ADDIE rules, valid media, and have received a very good response for application in science learning activities on food webs.